Shopaholic & sister - Kinsella, Sophie (Black Swan, 2004)
Becky thought being married to luke brandon would be one big tiffany box of happiness. But to be honest, it s not quite as dreamy as she d hoped. The trouble started on honeymoon, when she told luke the tiniest little fib, about the teeniest little purchase. Now she s on a strict budget, she doesn t have a job - and worst of all her beloved suze has a new best friend. Then she receives some incredible news. She has a long-lost sister! Becky has never been more excited. Finally, a real sister! They ll have so much in common! They can go shopping together...choose shoes together...have manicures together...until she meets her - and gets the shock of her life. It can t be true. Surely becky bloomwood s long-lost sister can't...hate shopping? A sister, a soulmate, a skinflint?